Associations between adherence to the Taiwan Daily Food Guide and psychiatric morbidity: A population-based study in Taiwan - Li, Ming-Chieh (Frontiers in Psychiatry, 2022)
Background: Mental health has become a public health concern worldwide, and the number of affected individuals is rising. Therefore, further research must be conducted to identify potential risk factors to develop optimal prevention strategies to mitigate mental health disorders. Methods: Using Taiwanese Nutrition and Health Survey data collected from 2013–2016, we conducted a cross-sectional study to examine whether adherence to the Taiwan Daily Food Guide affects mental health conditions. Study participants were adults aged ≥ 19 years. The dietary assessment was conducted using a validated food frequency questionnaire. The presence of psychiatric morbidity was defined as a five-item Brief Symptom Rating Scale (BSRS-5) score of ≥ 10. Logistic regression models were used to determine whether Taiwan Daily Food Guide adherence was related to the presence of psychiatric morbidity. Results: After adjusting for potential confounders, we observed protective associations between adherence to the Taiwan Daily Food Guide and psychiatric morbidity risk. Conclusion: The Taiwan Daily Food Guide might reduce the risk associated with psychiatric morbidity and could be a reference for developing a national food guide for mental health.